Strengthening decision-making on sustainable agricultural intensification through multi-stakeholder social learning in sub-Saharan Africa - Lamboll, R.; Nelson, V.; Gebreyes, Million; Kambewa, D.; Chinsinga, B.; Karbo, N.; Rukonge, A.; Sekeleti, M.; Wakun'uma, W.; Gutema, T.; Henjewele, M.; Phiri, J.; et al. (Informa UK Limited, 2021)
Increasing and competing demands on agriculture in sub-Saharan Africa mean that policy and investment decisions become more complex. Despite growing consensus on the need for sustainable agricultural intensification, there is limited agreement on how to achieve this in practice. Governments and societies face uncertainty and complex choices. This paper explores the potential of Multi-Stakeholder, Social Learning (MSL) approaches, facilitated by National Learning Alliances (NLAs), to improve policy and investment decisions. Comparative evidence from a donor-supported research and learning programme in Ethiopia, Ghana, Malawi, Tanzania and Zambia is used in a theory-based evaluation approach to assess the contribution of the NLAs to capacity and practice change amongst individuals, networks and senior decision-makers. Ten outcome cases are explored, including their contribution to systemic changes in the governance of evidence. Key lessons included: the value to decision-makers of engaging with informal networks; importance of combining dialogue, deliberation and experiential learning; the need to create safe spaces in national level MSL processes; the demanding combination of facilitation skills and commitment; and appropriately flexible support. This suggests a need not only for the production of quality research, but crucially support for MSL as a means of contributing to the good governance of evidence and sustainable change.